Cytokinesis in Suspension: A Distinctive Trait of Mesenchymal Stem Cells - Bhavna Rani; Hong Qian; Staffan Johansson (Cells)
Mesenchymal stem cells (MSCs) have a broad clinical potential, but their selection and expansion on plastic cause unknown purity and phenotypic alterations, reducing therapy efficiency. Furthermore, their behavior in non-adherent conditions during systemic transplantation remains poorly understood. The sphere formation from single cells is commonly used to assess stemness, but MSCs lack this ability, raising questions about their anchorage dependence for proliferation. We investigated whether bone marrow-derived MSCs can complete cytokinesis in non-adherent environments. Primary human and mouse bone marrow-derived MSCs were synchronized in early mitosis using nocodazole and were cultured on soft, rigid, or non-adherent surfaces. Both human and mouse MSCs displayed an ALIX (abscission licensor) recruitment to the midbody 40–90 min post-nocodazole release, regardless of the substrate adherence. Cells maintained for 4hr in the suspension remained viable, and daughter cells rapidly migrated apart upon the re-adhesion to fibronectin-coated surfaces, demonstrating cytokinesis completion in suspension. These findings distinguish MSCs from fibroblasts (which require adhesion for division), provide a more general stemness feature, and suggest that adhesion-independent cytokinesis is a trait relevant to the post-transplantation survival and tissue homing. This property may offer strategies to expand MSCs with an improved purity and functionality and to enhance engraftment by leveraging cell cycle manipulation to promote an early extracellular matrix deposition at target sites.